The nature of active sites of Ni2P electrocatalyst for hydrogen evolution reaction - Moon, Ji-Sue; Jang, Jue-Hyuk; Kim, Eung-Gun; Chung, Young-Hoon; Yoo, Sung Jong; Lee, Yong-Kul (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2015)
Nano-scaled Ni2P particles were synthesized by ligand stabilization method and applied for hydrogen evolution reaction (HER). X-ray diffraction (XRD), transmission electron microscope (TEM), and X-ray absorption fine structure (XAFS) spectroscopy were employed to examine structural properties of Ni2P nanoparticles. The electrocatalytic HER activity and stability for the Ni2P nanocatalyst were tested in 0.5M H2SO4, and the Ni2P electrocatalyst exhibited a low onset potential for the HER at around -0.02 V vs. RHE, a little more negative compared to the Pt catalyst which shows almost 0 V vs. reversible hydrogen electrode (RHE), and the Tafel slope of 75 mV per decade, i.e. following Volmer step as a rate-determining step. Density functional theory (DFT) calculations for hydrogen adsorption over Ni2P surfaces (001) and (002) revealed that the hydrogen adsorption might occur via two reaction pathways: consecutive or simultaneous hydrogen adsorption. The consecutive hydrogen adsorptions on threefold hollow (TFH)-Ni site followed by on P(II) site on a Ni2P (001) surface led to a lower reaction barrier than simultaneous hydrogen adsorption. These results thus demonstrated that the Volmer step might follow consecutive adsorption mechanism over the Ni2P surface. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: NICKEL PHOSPHIDE; CATALYSTS; HYDRODESULFURIZATION; PLATINUM; CARBIDE